UNEMPLOYMENT INSURANCE RESEARCH AND THE GOVERNANCE OF INDONESIA’S JOB LOSS GUARANTEE PROGRAM: A GLOBAL BIBLIOMETRIC ASSESSMENT AND SYSTEMATIC LITERATURE REVIEW: UNEMPLOYMENT INSURANCE RESEARCH AND THE GOVERNANCE OF INDONESIA’S JOB LOSS GUARANTEE PROGRAM: A GLOBAL BIBLIOMETRIC ASSESSMENT AND SYSTEMATIC LITERATURE REVIEW - Iskandar, Adriyansya; Hamzah, Muhammad Zilal; Sofilda, Eleonora; Nurhayati, Nurhayati (PENANOMICS: International Journal of Economics, 2025)
This study analyses global research trends on unemployment insurance (UI) alongside Indonesia’s Job Loss Guarantee programme (Jaminan Kehilangan Pekerjaan/JKP) by integrating bibliometric analysis and a systematic literature review. Drawing on 16,181 Scopus-indexed publications from 2010 to 2025, the bibliometric findings indicate a clear transition from early conceptual debates to rapid scholarly expansion after 2018, largely triggered by the COVID-19 pandemic and subsequent labour market reforms. Recent research increasingly focuses on adaptive UI systems that emphasise activation policies, digital governance, and reemployment support. A PRISMA-guided review identifies seven empirical studies relevant to Indonesia, examining ALMPs, JKP implementation, labour mobility, behavioural responses to job loss, unemployment forecasting, and skilled-worker vulnerability. Overall, Indonesia’s contribution to UI scholarship remains modest and predominantly descriptive, with limited methodological depth. Persistent challenges include weak institutional coordination, low public awareness of JKP, mismatched training provision, and restricted access for informal workers. The study highlights critical research gaps in impact evaluation, policy integration, and regional variation. Policy recommendations stress stronger governance coordination, data-driven activation mechanisms, and targeted skills development to enhance labour market protection in Indonesia.